TMIC-03. UPREGULATION OF THE NLRC4 INFLAMMASOME CONTRIBUTES TO POOR PROGNOSIS IN GLIOMA PATIENTS. (11th November 2019) - Lim, Jaejoon; Park, Youngjoon; Kim, Minjun; Ahn, Juwon; Kwack, KyuBum; Cho, Kyunggi
Abstract: Inflammation in tumor microenvironments is implicated in the pathogenesis of tumor development. In particular, inflammasomes, which modulate innate immune functions, are linked to tumor growth and anticancer responses. However, the role of the NLRC4 inflammasome in gliomas remains unclear. Here, we investigated whether the upregulation of the NLRC4 inflammasome is associated with the clinical prognosis of gliomas. We analyzed the protein expression and localization of NLRC4 in glioma tissues from 11 patients by immunohistochemistry. We examined the interaction between the expression of NLRC4 and clinical prognosis via a Kaplan-Meier survival analysis. The level of NLRC4 protein was increased in brain tissues, specifically, in astrocytes, from glioma patients. NLRC4 expression was associated with a poor prognosis in glioma patients, and the upregulation of NLRC4 in astrocytomas was associated with poor survival. Furthermore, hierarchical clustering of data from the Cancer Genome Atlas dataset showed that NLRC4 was highly expressed in gliomas relative to that in a normal healthy group. Our results suggest that the upregulation of the NLRC4 inflammasome contributes to a poor prognosis for gliomas and presents a potential therapeutic target and diagnostic marker.